On proton synchrotron blazar models: the case of quasar 3C 279 - Petropoulou, M.; Mastichiadis, A. (2012)
In this work we propose an innovative estimation method for the minimum Doppler factor and energy content of the γ-ray emitting region of quasar 3C 279, using a standard proton synchrotron blazar model and the principles of automatic photon quenching. The latter becomes relevant for high enough magnetic fields and results in spontaneous annihilation of γ-rays. The absorbed energy is then redistributed into electron-positron pairs and soft radiation. We show that as quenching sets an upper value for the source rest-frame γ-ray luminosity, one has, by necessity, to resort to Doppler factors that lie above a certain value in order to explain the TeV observations. The existence of this lower limit for the Doppler factor also has implications on the energetics of the emitting region. In this aspect, the proposed method can be regarded as an extension of the widely used method for estimating the equipartition magnetic field using radio observations. In our case, the leptonic synchrotron component is replaced by the proton synchrotron emission and the radio by the very high energy γ-ray observations. We show specifically that one can model the TeV observations by using parameter values that minimize both the energy density and the jet power at the cost of high values of the Doppler factor. On the other hand, the modelling can also be done by using the minimum possible Doppler factor; this, however, leads to a particle-dominated region and high jet power for a wide range of magnetic field values. Despite the fact that we have focused on the case of 3C 279, our analysis can be of relevance to all TeV blazars favouring hadronic modelling that have, moreover, simultaneous X-ray observations.
Keywords: astroparticle physics; Astrophysics - High Energy Astrophysical Phenomena; galaxies: active; gamma-rays: galaxies; radiation mechanisms: non-thermal